GDF15(MIC1) H6D Polymorphism Does Not Influence Cardiovascular Disease in a Latin American Population with Rheumatoid Arthritis - Jenny Amaya-Amaya; Adriana Rojas-Villarraga; Nicolas Molano-Gonzalez; Laura Montoya-Sánchez; Swapan K. Nath; Juan-Manuel Anaya (Journal of Immunology Research)
Objective. Rheumatoid arthritis (RA) is the most common autoimmune arthropathy worldwide. The increased prevalence of cardiovascular disease (CVD) in RA is not fully explained by classic risk factors. The aim of this study was to determine the influence of rs1058587 SNP within GDF15(MIC1) gene on the risk of CVD in a Colombian RA population. Methods. This was a cross-sectional analytical study in which 310 consecutive Colombian patients with RA and 228 age- and sex-matched controls were included and assessed for variables associated with CVD. The mixed cluster methodology based on multivariate descriptive methods such as principal components analysis and multiple correspondence analyses and regression tree (CART) predictive model were performed. Results. Of the 310 patients, 87.4% were women and CVD was reported in 69.5%. Significant differences concerning GDF15 polymorphism were not observed between patients and controls. Mean arterial pressure, current smoking, and some clusters were significantly associated with CVD. Conclusion. GDF15 (rs1058587) does not influence the development of CVD in the population studied.